The Project-Based Learning’s Key Characteristic: How STEAM Sparks Creativity and Curiosity in Cultivating Daphnia sp. Acid-Based Chemistry - Inas Sausan; Faizal Adi Akhmad Masbukhin (JKPK (Jurnal Kimia dan Pendidikan Kimia), 2024)
This study explores the integration of STEAM (Science, Technology, Engineering, Arts, Mathematics) with Project-Based Learning (PBL) to enhance creativity and curiosity in high school students within the context of chemistry education. The research involved 11th-grade students designing a Daphnia sp. cultivation pond, a project aimed at applying interdisciplinary knowledge and fostering essential 21st-century skills. Using a qualitative case study approach, data were collected through questionnaires, interviews, and student worksheets. The study focuses on an in-depth analysis of six key characteristics of STEM-PBL including driving questions, learning goals, scientific practice, collaboration, using a technological tool, and creating an artifact—creativity and curiosity as key outcomes. The results indicate a significant positive correlation between creativity and students' cognitive performance, highlighting the effectiveness of the STEAM-PBL approach in promoting innovative thinking and problem-solving skills. However, the study found no significant relationship between curiosity and cognitive scores, suggesting that curiosity may develop independently of direct academic outcomes within this framework. Despite these positive findings, the study also identified challenges such as limited resources, insufficient teacher training, and resistance to traditional educational methods. The study recommends further exploration into the long-term impacts of STEAM-PBL and its applicability across different educational contexts.